2021
DOI: 10.1111/hiv.13050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of dolutegravir two‐drug regimens in virologically suppressed people living with HIV: a systematic literature review and meta‐analysis of real‐world evidence

Abstract: Dolutegravir (DTG) is widely recommended within three-drug regimens. However, similar efficacy and tolerability have also been achieved with DTG within two-drug regimens in clinical trials. This study evaluated the real-world effectiveness and discontinuations in people living with HIV-1 (PLHIV) switching to DTG with lamivudine (3TC) or rilpivirine (RPV). MethodsThis was a one-arm meta-analysis utilizing data from a systematic literature review. Data from real-world evidence studies of DTG + RPV and DTG + 3TC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
6
23
0
1
Order By: Relevance
“…Even with the discovery of treatment, HIV infection remains a major public health problem in the world. Despite the proven efficacy of triple therapy with tenofovir, lamivudine, and dolutegravir (TDF + 3TC + DTG), predicting resistance and adverse events in patients on this regimen is a necessity to monitor virological failure (VF) [1,2], especially in resource-limited countries stricken by political and security instability. Antiretroviral therapy (ART) is aimed at achieving an undetectable viral load (VL) (<50 copies/mL) within 6 months of treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the discovery of treatment, HIV infection remains a major public health problem in the world. Despite the proven efficacy of triple therapy with tenofovir, lamivudine, and dolutegravir (TDF + 3TC + DTG), predicting resistance and adverse events in patients on this regimen is a necessity to monitor virological failure (VF) [1,2], especially in resource-limited countries stricken by political and security instability. Antiretroviral therapy (ART) is aimed at achieving an undetectable viral load (VL) (<50 copies/mL) within 6 months of treatment initiation.…”
Section: Introductionmentioning
confidence: 99%
“…In this open label clinical trial, switching to DTG/3TC achieved a similar virological response to the control arm (93.2% vs. 93%, respectively) [26]. Furthermore, several real-life cohort studies have also found a great virological response in patients treated with DTG/3TC [35].…”
Section: Integrase Strand Transfer Inhibitor-based 2drmentioning
confidence: 57%
“…A recent systematic review and meta-analysis explored real-world effectiveness and tolerability of DTG/3TC in virologically suppressed patients and documented long-term virological outcomes consistent with findings from randomised clinical trials. 10 Although there is clinical evidence of the safety, effectiveness and tolerability of dual-drug regimens, [11][12][13][14][15][16] there is limited insight into patient experiences and perceptions of dual-drug combinations, including the DTG/3TC regimen. A qualitative study conducted in the USA and in Spain explored patients' perspectives and experiences in 39 patients on dual-drug combinations and documented that participants viewed dual-drug regimens as a significant and positive advance, in terms of its effectiveness, with reduced toxicity and essentially no reported side effects.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%